Late pandemic COVID-19 positivity at the time of thrombectomy is associated with poor outcomes and tandem carotid pathology - Lewis John Rubin Thompson; Clifton Houk; Nathaniel R. Ellens; Gurkirat Singh Kohli; Derrek Schartz; Diana Proper; Tarun Bhalla; Matthew T. Bender; Thomas K. Mattingly (Frontiers in Neurology)
ObjectivesCOVID-19 is an independent risk factor for ischemic stroke. Studies from early in the pandemic show increased rates of unfavorable recanalization, poor outcomes, and mortality in patients who were COVID-19 positive at the time of mechanical thrombectomy. However, there are currently no studies examining these parameters during the later pandemic when circulating variants were less virulent.Materials and methodsWe performed a retrospective review of mechanical thrombectomies from 12/2020 to 3/2023. Patients who were COVID-19 positive at the time of thrombectomy were included. Demographic, procedural, and 90-day functional outcomes were evaluated.ResultsOf 306 patients undergoing mechanical thrombectomy for acute ischemic stroke between 12/2020 and 3/2023, 18 were COVID-19 positive. Compared with the COVID-19 negative cohort, there were lower rates of favorable recanalization (73% vs. 92%, p = 0.03) and good functional outcomes (26% vs. 49%, p = 0.06), but greater tandem carotid pathology (42% vs. 12%, p < 0.01), and a higher mortality rate (53% vs. 26%, p = 0.02). However, COVID-19 positive status did not predict outcomes in multivariable analysis when controlled for age, NIHSS, IV tPA, recanalization status, and tandem carotid pathology.ConclusionLate in the pandemic, outcomes remained comparable to those observed in the early pandemic for patients positive for COVID-19 at the time of mechanical thrombectomy. This case series also demonstrates increased tandem carotid pathology in the COVID-19 cohort. While COVID-19 may not influence outcome to the degree that age and NIHSS do, the excess mortality continues to suggest a negative effect despite lower virulence.